Community, conflict and social change: The case of the Southern Peru Copper Corporation - Bauch, Elizabeth (1985)
This article has two purposes: to present historical and ethnographic data on the Southern Peru Copper Corporation, especially its camps in Ilo and Toquepala; and place the data in an analytical perspective that allows us to draw not only conclusions about the trajectory of this company and its workforce, but also help us understand the labor process within the system of transnational capitalism in various parts of the world. We postulate that the international economic system, capitalism, is constantly transforming.